Human Security Situation and State Police Establishment Contention in Nigeria - Egbadju, Obukohwo Abraham; Ikenga, Francis Ayegbunam; Otite, Atare (LPPM Universitas Malikussaleh, 2023)
This study examined human security situation and state police establishment contention in Nigeria. This theoretical paper draws its arguments primarily from secondary sources of data, such as journal publications and textbooks. The study concluded that the capacity of the Police is further reduced due to the deployment of a good number of policemen to undertake guard duties and private security services for the rich and affluent in the society. Perhaps, the greatest impediment to police effectiveness in Nigeria remains corruption. The limited funds meant for security and other developmental purposes are diverted by those responsible for their utilization. This creates an unending vicious cycle of poverty, deprivation, greed, exploitation, unemployment and general underdevelopment that culminates in weakening the capacity of government to provide social services, fund security ultimately undermining national security. This study recommended a reform which would pave way for state police formations and give power to state governors over the police contingents in their states.